Clinical correlation between hypercalciuria and nocturnal enuresis - Ehsan Valavi; Ali Ahmadzadeh; Nakisa Hooman; Majid Aminzadeh (Saudi Journal of Kidney Diseases and Transplantation, 2011)
Hypercalciuria may present with dysuria, urinary incontinence and nocturnal enuresis (NE). To determine the frequency of hypercalciuria in NE patients and normally continent children, we studied 122 consecutive pre- school children with NE referred to our nephrology clinic during two years, from September 2007 to August 2009. We measured the 24- hour urinary calcium. Furthermore, we compared the response to nasal desmopressin in hypercalciuric and normocalciuric patients. Hypercalciuria was found in 26 (21.3 %) of the NE patients as compared with five (4.5%) of 110 continent children [(P < 0.001), OR = 5.68 (95% CI, 2.1-15.4)]. In addition, the mean 24- hour urine calcium/body weight ratio (24h- U- Ca/Bw) was higher in NE patients, 3.04 ± 1.54 vs. 2.57 ± 0.9, respectively (P = 0.005). Wet nights per week in both NE patients with and without hypercalciuria at the first visit ranged from two to seven (median: 6 and 7, respectively), and the mean overall success rate of the nasal desmopressin therapy was 83.3% and 90%, respectively (P > 0.05). The response to desmopressin above 90% occurred within one month of therapy without a significant change in the levels of hypercalciuria. We conclude that these results suggest that hypercalciuria has a significant association with NE and does not interfere with the desmopressin therapy.